Nanovate Commercializing Disruptive Nanotechnologies - Anis, Mohab; AlTaher, Ghada; Sarhan, Wesam; Elsemary, Mona.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book introduces readers from diverse backgrounds to the principles underlying nanotechnology, from devices to systems, while also describing in detail how businesses can use nanotechnology to redesign their products and processes, in order to have a clear edge over their competition. The authors include 75 case studies, describing in a highly-accessible manner, real nanotechnology innovations from 15 different industrial sectors. For each case study, the technology or business challenges faced by the company are highlighted, the type of nanotechnology adopted is defined, and the eventual economic and social impact is described. Introduces fundamentals of nanotechnology and its applications in a highly-accessible manner Includes 75 case studies of commercializing nanotechnology from 15 industrial sectors, including Automotive, Consumer Electronics, and Renewable Energy Enables nanotechnology experts to learn simple and important business concepts to facilitate the transfer of science to the market Introduces business owners to various means to resolve industrial challenges using nanotechnologies.
Introduction -- Construction and Building Applications -- Manufacturing Applications -- Clean Energy Applications -- Environment and Remediation Applications -- Electronic Applications -- Printing Applications -- Textile Applications -- Sports Equipment -- Nutraceutical Industry -- Packaging Applications -- Agricultural Applications -- Cosmetic Applications -- Pharmaceutical Applications -- Conclusions.
Keywords: Electronic circuits; Microtechnology; Microelectromechanical systems; Renewable energy sources; Automotive engineering; Electronic Circuits and Systems; Microsystems and MEMS; Renewable Energy; Automotive Engineering